Sensitivity to tumor development by TALEN-mediated Trp53 mutant genes in the susceptible FVB/N mice and the resistance C57BL/6 mice - Woo Bin Yun (BMC, 2021)
Abstract Background This study was undertaken to compare the sensitivities of mice strains during tumor induction by transcription activator-like effector nucleases (TALEN)-mediated Trp53 mutant gene. Alterations of their tumorigenic phenotypes including survival rate, tumor formation and tumor spectrum, were assessed in FVB/N-Trp53em2Hwl/Korl and C57BL/6-Trp53em1Hwl/Korl knockout (KO) mice over 16 weeks. Results Most of the physiological phenotypes factors were observed to be higher in FVB/N-Trp53em2Hwl/Korl KO mice than C57BL/6-Trp53em1Hwl/Korl KO mice, although there were significant differences in the body weight, immune organ weight, number of red blood cells, mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), platelet count (PLT), total bilirubin (Bil-T) and glucose (Glu) levels in the KO mice relative to the wild type (WT) mice. Furthermore, numerous solid tumors were also observed in various regions of the surface skin of FVB/N-Trp53em2Hwl/Korl KO mice, but were not detected in C57BL/6-Trp53em1Hwl/Korl KO mice. The most frequently observed tumor in both the Trp53 KO mice was malignant lymphoma, while soft tissue teratomas and hemangiosarcomas were only detected in the FVB/N-Trp53em2Hwl/Korl KO mice. Conclusions Our results indicate that the spectrum and incidence of tumors induced by the TALEN-mediated Trp53 mutant gene is greater in FVB/N-Trp53em2Hwl/Korl KO mice than C57BL/6-Trp53em1Hwl/Korl KO mice over 16 weeks.